METODE MONTESSORI UNTUK MENGEMBANGKAN KARAKTER KEMANDIRIAN AUD DALAM PERSPEKTIF ISLAM - Nida Adilah; A. Yuri Alam F. (STIT AL-AMIN KREO TANGERANG, 2023)
The first 1000 days of a child's life is the golden age. In this period, various potentials develop in children. Among them, physical abilities, cognitive, affective, language, arts, social, emotional, moral, self-concept, independence, discipline, and religion. Independence and discipline are important parts of the concern of the Montessori method. In the Montessori method, adults provide full freedom and support for children's independence, through various types of activities. Children are allowed to observe and intervene in the types of daily activities, so that children will be more interested, responsible and concentrate on the tasks they are doing. So, in the end the child will achieve the character education process through the daily activities that have been carried out. In this study, we will briefly describe the combination of Islamic concepts and Montesori methods, especially for building character education, especially independence in children. The primary source in this study is the writings of Maria Montessori which have been translated into Indonesian entitled The Absorbent Mint